Global diversity of earthworms and enchytraeids (Clitellata): papers in honor of András Zicsi (1928–2015). Editorial - Schmelz, Rüdiger M. (Zootaxa, 2018)
This Special Volume of Zootaxa unites forty papers written in honor of the late András Zicsi (1928–2015), the eminent earthworm taxonomist. They deal with the taxonomy, systematics and distribution of earthworms and enchytraeids, the two major groups of soil-dwelling Oligochaeta. Altogether, 71 new species-group taxa are described, 60 species and subspecies of earthworms and 11 species of enchytraeids. They are from 15 countries all around the globe: Spain, Italy, Hungary, Turkey, Botswana, Mexico, Colombia, Brazil, China, Japan, Korea, Taiwan, Laos, Malaysia, Thailand, and Vietnam.